Literature Review of Digital Literacy on Human Resources Management - Setyawantika, Mokhamad Arif; Hamidah; Fauzi, Achmad (IJHCM (International Journal of Human Capital Management), 2024)
The integration of digital technology in the workplace has transformed job roles, resource allocation, and employee anticipation. Especially amid the Covid-19 pandemic, the digitalization of workplaces has seemingly necessitated employees to acquaint themselves with, excel at, and utilize these technologies within their professional settings. This trend has spurred the rise of the notion of digital literacy among the workforce. Therefore this research aims to investigate the literature review of digital literacy using grounded theory model. Furthermore, there were 14 journal articles collected indexed in Scopus Q1, with 3 articles, 8 articles from journals indexed in Scopus Q2, 2 articles indexed in Q3, and 1 article indexed in Q4. Therefore, research articles with the theme of digital literacy in human resources. Each article was served to explain the variable position.As a result, (1) digital literacy serving as a crucial factor in nurturing innovation at both individual and organizational scales; (2) factors that determine the success of technology implementation; and (3) indicators of enhanced performance. This highlights the significance of digital literacy in the advancement of Human Resources Management, aiming to cultivate innovation and digital ethos within organizations amidst the prevailing era of digitalization